Radiographic evaluation of the prevalence of residual roots with indication for rehabilitation with an intraradicular retainer (Research, Society and Development, 2023)
The aim of the study is to evaluate the prevalence of residual roots that can be rehabilitated with the use of an intraradicular retainer, through panoramic radiographs of patients seen at the dental clinic of ITPAC-Palmas. To this end, 189 radiographs were randomly selected, with ages ranging from 14 to 80 years. All patients who attended the clinic for this imaging exam between January 2019 and December 2022 were included. The images were evaluated by the examiners with the aid of the CLINIVIEW software to visualize the teeth classified as residual roots. The roots were measured with the calibrated ruler tool of the software, and were considered suitable for rehabilitation with the use of retainers the elements that presented at least 2 mm of coronary remnant and 10 mm of root, for adaptation of the prefabricated pin in 2/3 so that over 3 to 4 mm for the filling material. The results show that 74 patients were male and 115 were female. Of these, only 24 patients had residual roots, with a total of 48 roots that were evaluated. We conclude that the prevalence of patients with residual roots was 13%, and it was more common in the 20-40 age group. We highlight the importance of a careful evaluation of residual roots to define the best clinical outcome, taking into account individual factors. In addition, the authors suggest that panoramic radiography may present difficulties in the evaluation of residual roots.